FROM PARABOLA THEORY TO PARABOLIC ANTENNA: ELECTRICAL PRACTICE - Komiljonov Bobur Komiljon ugli; Khalilov Murodiljon Durbek ugli (Bright Mind Publishing, 2025)
In this article, the parabola topic, which is part of the "second-order curves" section of higher mathematics, is integrated with electrical engineering. The theoretical foundations, geometric properties, and analytical equations of parabolas are illustrated using a practical example - a parabolic antenna. In the study, a mathematical model was constructed based on the dimensions of the offset parabolic antenna, widely used in home conditions, and such parameters as focal length, directrix, depth, eccentricity were calculated. Analytical geometry and computational methods were used as the research methodology. This approach strengthens the practical aspect of higher mathematics and serves to deepen students' understanding of the topic. This approach is also an effective way of interdisciplinary integration.
Keywords: parabola, parabolic antenna, second-order curves, focus, directrix, eccentricity, offset antenna, analytic geometry.